Level of Exposure Elementary School Teachersto the Implementation Merdeka Curriculum - Umar; Syarifuddin; Jayanti, Mei Indra; Irwan; Indrawan (LETIGES, 2024)
This study aims to analyse the perceptions and level of exposure of undergraduate primary school teacher candidates to implementing the Merdeka curriculum. The research used a descriptive survey method involving 44 prospective elementary school teacher students from Muhammadiyah Bima University who were selected as survey respondents. Research data was collected using a questionnaire item that was numerically assessed and distributed via Google Forms. Then the research data, analysed using descriptive statistics and percentages to describe the characteristics of the data and respondents in seeing changes in the merdeka curriculum implementation policy in Bima City in the form of tables, graphs, or diagrams to facilitate interpretation. The research findings revealed that around 51% of elementary school prospective teachers fall into the category of moderate exposure to the Merdeka Curriculum. In comparison, 44% have low exposure, and only 5% have high exposure to information and implementation of the Merdeka Curriculum. This condition is influenced by several factors, among which the most significant factor affecting elementary school teacher candidates is motivation, with 67.4% motivated to explore the Merdeka curriculum. The survey also depicts the most common forms of support provided by the university, including the use of learning resources related to the Merdeka curriculum (41.9%), support through applications in courses (39.5%), support through the dissemination of information about Merdeka curriculum seminars, and some do not provide any support or mentoring (4.7%). Prospective teachers make various efforts to improve their understanding of the independent curriculum implementation policy, such as attending seminars and workshops on the Merdeka curriculum, seeking information independently from reading sources both from textbooks and online sources, discussing with lecturers, and being directly involved in the implementation of the independent curriculum.